Ugrading Digital Marketing UMKM Produsen Gula Juruh di Desa Terusan Kempas Gaung - Kamaruzzaman; Ramadani, Nia; Apriani, Risma; Sari, Ratna; Hera Ravida MJ; Husaini, Ahmad; Azizi, Khairul; Geri, Nove; Adi Putra, Bambang Sasmita (Indra Institute Research & Publication, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main pillars of the economy, contributing significantly to community welfare, including coconut-based palm sugar producers. However, they often face problems such as simple packaging, the absence of a brand identity, lack of business legality, and reliance on traditional marketing strategies, which limit product competitiveness. This community service program aimed to strengthen the capacity of palm sugar producers by providing training and mentoring in four key areas: hygienic and attractive product packaging, the creation of a local brand with consumer appeal, assistance in obtaining business legality through the issuance of a Business Identification Number (NIB), and the use of digital marketing strategies through social media and marketplaces. The method applied was Participatory Action Research (PAR), directly involving MSME actors at every stage from problem identification, planning, implementation, to evaluation. The results showed improved technical skills, the establishment of the local brand “Gula Juruh Angah Unggal,” the successful issuance of a business license (NIB), and the adoption of digital marketing strategies tested through sales at a local bazaar with positive consumer responses. In conclusion, this program effectively enhanced the competitiveness of palm sugar MSMEs, although sustainability requires further mentoring, halal certification, and stronger marketing networks.